Insights into Stability and Folding of GNRA and UNCG Tetraloops Revealed by Microsecond Molecular Dynamics and Well-Tempered Metadynamics - Haldar, Susanta; Kührová, Petra; Banáš, Pavel; Spiwok, Vojtěch; Šponer, Jiří; Hobza, Pavel; Otyepka, Michal (Journal of chemical theory and computation, 2015)
RNA hairpins capped by 5'-GNRA-3' or 5'-UNCG-3' tetraloops (TLs) are prominent RNA structural motifs. Despite their small size, a wealth of experimental data, and recent progress in theoretical simulations of their structural dynamics and folding, our understanding of the folding and unfolding processes of these small RNA elements is still limited. Theoretical description of the folding and unfolding processes requires robust sampling, which can be achieved by either an exhaustive time scale in standard molecular dynamics simulations or sophisticated enhanced sampling methods, using temperature acceleration or biasing potentials. Here, we study structural dynamics of 5'-GNRA-3' and 5'-UNCG-3' TLs by 15-μs-long standard simulations and a series of well-tempered metadynamics, attempting to accelerate sampling by bias in a few chosen collective variables (CVs). Both methods provide useful insights. The unfolding and refolding mechanisms of the GNRA TL observed by well-tempered metadynamics agree with the (reverse) folding mechanism suggested by recent replica exchange molecular dynamics simulations. The orientation of the glycosidic bond of the GL4 nucleobase is critical for the UUCG TL folding pathway, and our data strongly support the hypothesis that GL4-anti forms a kinetic trap along the folding pathway. Along with giving useful insight, our study also demonstrates that using only a few CVs apparently does not capture the full folding landscape of the RNA TLs. Despite using several sophisticated selections of the CVs, formation of the loop appears to remain a hidden variable, preventing a full convergence of the metadynamics. Finally, our data suggest that the unfolded state might be overstabilized by the force fields used.
Keywords: simulace molekulární dynamiky; vodíková vazba; Base Sequence; sekvence nukleotidů; konformace nukleové kyseliny; RNA; Nucleic Acid Conformation; Molecular Dynamics Simulation; Hydrogen Bonding; Nucleic Acid Denaturation; Proteins; proteiny; denaturace nukleových kyselin